Transferência de conhecimento em projetos de manutenção de plataformas offshore : um estudo de caso - Cunha, Marcela de Faria (2018)
Offshore oil platform maintenance campaigns, supported by a Unit for Maintenance and Safety (UMS), present particularities that make them complex, such as: long planning time; high variability and difficulties inherent to the offshore maintenance activities; involvement of an important group of professionals; temporarily cut oil production; among others. In order to understand how the formal knowledge transfer process is developed among these platforms maintenance projects, a case study was carried out in a Brazilian oil exploration and production company. The study object of the research was the process formally structured by lessons learned events, which include the identification and dissemination of knowledge items, as well as the database for registration and consultation of content. This process occurs in the closing phase of the project life cycle. In this context, this work presents an analysis of the formal knowledge transfer process undertaken by the organization, in which it seeks to identify and discuss its contributions and limitations. From this, possible process improvement opportunities emerge. Above all, the research emphasizes aspects of social participation in knowledge management, based on regular interactions that improve learning.